2017
DOI: 10.1161/circresaha.116.310480
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Mineralocorticoid Receptor Controls Blood Pressure by Regulating Interferon-Gamma

Abstract: MR may interact with NFAT1 and activator protein-1 to control IFN-γ in T cells and to regulate target organ damage and ultimately BP. Targeting MR in T cells specifically may be an effective novel approach for hypertension treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 48 publications
3
76
0
2
Order By: Relevance
“…31 Recent studies have shown that MR activation promotes T lymphocyte Th17 polarization and reduced the number of Foxp3 + T regulatory cells, effects that were associated with | 3 of 9 BARRERA-CHIMAL And JAISSER aldosterone-induced cardiac and renal damage. 33 It has also been shown that the MR can interact with nuclear factor of activated T cells (NFAT) and activator-protein-1, thus showing that the MR may be important for T-cell activation. Mice with T cells lacking the MR are protected against hypertension induced by angiotensin II and show decreased vascular and renal damage through a mechanism involving a reduced number of interferon-gamma producing T cells.…”
Section: Mr Activation Modulates the Activation Of T Cells And Macrmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Recent studies have shown that MR activation promotes T lymphocyte Th17 polarization and reduced the number of Foxp3 + T regulatory cells, effects that were associated with | 3 of 9 BARRERA-CHIMAL And JAISSER aldosterone-induced cardiac and renal damage. 33 It has also been shown that the MR can interact with nuclear factor of activated T cells (NFAT) and activator-protein-1, thus showing that the MR may be important for T-cell activation. Mice with T cells lacking the MR are protected against hypertension induced by angiotensin II and show decreased vascular and renal damage through a mechanism involving a reduced number of interferon-gamma producing T cells.…”
Section: Mr Activation Modulates the Activation Of T Cells And Macrmentioning
confidence: 99%
“…32 The use of transgenic mice lacking the MR in T cells has shed light on the role of the MR in T cells. 33 In macrophages, it was first shown that MR activation by aldosterone induces a pro-inflammatory signature characteristic of M1-activated macrophages, with increased expression of TNF-alpha, Monocyte chemoattractant protein-1 (MCP-1), RANTES and IL-12. 33 It has also been shown that the MR can interact with nuclear factor of activated T cells (NFAT) and activator-protein-1, thus showing that the MR may be important for T-cell activation.…”
Section: Mr Activation Modulates the Activation Of T Cells And Macrmentioning
confidence: 99%
“…20 Ventricular weight-to-body weight ratio demonstrated significantly less cardiac hypertrophy in TMRKO mice than in littermate control mice 1 and 6 weeks after AAC (Figure 2A). Hematoxilin and eosin staining of cross sections of left ventricles showed significantly decreased cardiomyocyte size in TMRKO mice after AAC ( Figure 2B; Figure S3A).…”
Section: T-cell Mr Deficiency Attenuates Aac-induced Cardiac Hypertromentioning
confidence: 95%
“…20 Male C57BL6/J mice were purchased from SLAC Laboratory Animal Co. Eplerenone was mixed in regular rodent chow (2 g/kg; SLAC Laboratory Animal Co.) and administrated 3 days before surgeries until the end of experiments to deliver a dosage of ≈200 mg/kg/d. Abdominal aortic constriction (AAC) was performed according to previous report.…”
Section: Animals and Surgeriesmentioning
confidence: 99%
“…5 The authors provide evidence that the Mineralocorticoid Receptor (MR) in T cells, and particularly in CD8 + T cells, modulates their production of interferon gamma (IFN-γ) and ultimately promotes hypertension. To accomplish this, the authors used Cre-Lox technology to eliminate the MR in all T cells, while leaving it intact in all other cells.…”
mentioning
confidence: 99%